Are social and traditional entrepreneurial intentions really that different?. Issue 7 (18th August 2021) - Santos, Susana C.; Nikou, Shahrokh; Brännback, Malin; Liguori, Eric W.
Abstract : Purpose: Building on construal level theory (CLT), this study explores mental representations of entrepreneurial intentions (EIs) with different foci (i.e. social and commercial) among university students from Generations Y and Z. Design/methodology/approach: Using a sample of university students from the United States contacted through the Entrepreneurship Education Project, this study employs a configurational perspective—fuzzy-set qualitative comparative analysis (fsQCA)—to identify the pathways leading to EIs and social entrepreneurial intentions (SEIs). Findings: Results show that the configurations of conditions leading to the outcomes (EI and SEI) are not disparate but share far more similarities even when considering socially oriented antecedents, supporting the claim that students perceive both EIs with different foci as high-level construals. The results also demonstrate no differences within gender, but there are asymmetries between gender in the configurations leading to EI and SEI. Research limitations/implications: This study contributes to EI literature by providing new insights into understanding how individuals perceive EIs at an early stage of entrepreneurship and by bringing CLT to the EI literature. Practical implications: These results have implications for entrepreneurship education and practice, as it recognizes that students' EIs are psychologically distant, lacking a level of detail and specificity. This would explain why students do not immediately create ventures, but that entrepreneurship has a certain incubation time to create an entrepreneurial mindset. Originality/value: Exploring the configurational approaches can help to uncover the complexity and idiosyncrasies underlying EIs.